Fluidity of Sn-based eutectic solder alloys - Morando, Carina Noemi (2015)
Eutectic alloys have a great importance in both academic and technological point of view. As regard technological applications such as casting, welding andjoining, these systems offer lower melting point than the pure elements, and good fluidity. The fluidity length (LF) is known as the distance travelled by the liquid metal forced to flow through a channel of small cross section, until it is stopped by solidification. Physical variables associated with the process are: metallostatic pressure, heat extraction rate at the metal-mold interface, overheating of the liquid metal and the physico-chemical properties of the metal or alloy (latent heat of fusion, density, viscosity, surface tension and solidification mode). In general, pure metals and alloys of eutectic composition have the highest values of fluidity, whilst intermediate composition alloys with greater solidification range show lesser fluidity lengths.Taking into account that the chemical composition plays an important role in the fluidity length by its relationship with the resulting microstructure, the aim of this work is to obtain fluidity values of binary and ternary lead-free metallic alloys in order to determine the relationships between the morphology and the fluidity length, and consequently, the influence on binary and ternary pro-eutectic alloys. Fluidity tests were carried out in a linear fluidity device, using lead-free Sn based alloys, extensively used for important industrial applications. The samples were characterized using optical microscopy, scanning electron microscopy and energy dispersive X-ray microanalysis.Usually, fluidity length (LF) depends on solidification mode, latent heat of fusion of the alloy and the fluidity of the phases present in the microstructure.